0290 Cancer risks among Canadian mining workers in a population-based cohort. (23rd June 2014) - Sritharan, Jeavana; Hardt, Jill; Koné, Anna; Harris, Anne; Saini, Jasmik; Demers, Paul
Abstract : Objectives: Mining workers in Canada may be exposed to several potential carcinogens including crystalline silica, various metals, and diesel exhaust. This study aimed to assess the risk of cancer among male mining workers employed in various Canadian mining sectors. Method: The Cohort was created by Statistics Canada through the linkage of the 1991 Canadian Census (long form) to the Canadian Mortality Database, Canadian Cancer Registry, and annual Tax Summary Files (1991–2006). This linkage resulted in a cohort of 1.1 million working males aged 25–74, including over 14 000 workers employed in the mining industry. Cox proportional hazards modelling was used to estimate hazard ratios (HR) and corresponding 95% confidence intervals, adjusted for age and region. Results: There were 700 cancers among 660 mining industry workers. There was an increased risk for rectal cancer (HR: 1.37, 1.01–1.88), particularly in gold mining (HR: 3.11, 1.47–6.56). Increased risks of kidney and prostate cancer were observed for coal mining (HR: 2.71, 1.12–6.57 and HR: 1.80, 1.10–2.94, respectively), and esophageal cancer in metal mining other than gold or iron (HR: 2.78, 1.13–6.80). There were also elevated risks for stomach and laryngeal cancer among mining workers. Conclusions: This study identified increased risks of rectal, kidney, prostate, and esophageal cancers among male mining industry workers employed in specific sectors. There are also a number of limitations and challenges that accompany the investigation. Our findings may have important implications for our understanding of occupational cancer risk factors and potential policy interventions in the mining industry.